Elvis and me - Presley, Priscilla 1945- (Putnam, 1985)
Elvis Presley and Priscilla Beaulieu were together fourteen years. This is Priscilla Presley's powerful and poignant story of her life with the most successful entertainer of all time.
Keywords: Presley, Elvis <1935-1977>; Presley, Priscilla Beaulieu; Presley, Elvis -- 1935-1977; Presley, Priscilla -- 1945-; Popmuziek; Rock musicians -- United States -- Biography; Rock musicians' spouses -- United States -- Biography; Autobiografie; USA; Biografie